2009
DOI: 10.1111/j.1365-313x.2009.03948.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of bZIP‐type transcription factors involved in carrot (Daucus carota L.) somatic embryogenesis

Abstract: SUMMARYSeed dormancy is an important adaptive trait that enables seeds of many species to remain quiescent until conditions become favorable for germination. Abscisic acid (ABA) plays an important role in these developmental processes. Like dormancy and germination, the elongation of carrot somatic embryo radicles is retarded by sucrose concentrations at or above 6%, and normal growth resumes at sucrose concentrations below 3%. Using a yeast one-hybrid screening system, we isolated two bZIP-type transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 50 publications
(117 reference statements)
0
50
0
Order By: Relevance
“…5, authors made an extensive analysis of the state of the art in relation to the participation of transcription factors in this process. An interesting finding is that the most frequent transcription factors found active during the induction of SE belong to the pathways of the metabolism of growth regulators, stress, and flower development (El Ouakfaoui et al 2010;Guan et al 2009).…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…5, authors made an extensive analysis of the state of the art in relation to the participation of transcription factors in this process. An interesting finding is that the most frequent transcription factors found active during the induction of SE belong to the pathways of the metabolism of growth regulators, stress, and flower development (El Ouakfaoui et al 2010;Guan et al 2009).…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…Seventy-five bZIP genes have been found in Arabidopsis (Arabidopsis thaliana) (Jakoby et al, 2002), 55 in grapevine (Vitis vinifera) (Liu et al, 2014), 89 in rice (Oryza sativa) (Nijhawan et al, 2007), 131 in soybean (Glycine max) (Liao et al, 2008), 92 in Sorghum (Sorghum vulgare) , and 125 in maize (Zea mays) (Wei et al, 2012). Plant bZIP proteins have been found to regulate the integration and development of many organs and tissues, including seed maturation and germination (Izawa et al, 1994;Toh et al, 2012), floral induction and development (Abe, 2005;Iven et al, 2010;Wigge, 2005), vascular development (Yin et al, 1997), embryogenesis (Guan et al, 2009;Shiota et al, 2008) and photomorphogenesis (Holm, 2002;Huang et al, 2012). They have also been found to be involved in responses to a variety of abiotic/biotic stimuli, for example, the expression of OSBZ8 in rice is strongly induced by ABA and positively correlated with salt resistance (Mukherjee et al, 2006), LIP19 functions as a molecular switch for low-temperature signal transduction in rice (Shimizu, 2005), the tobacco (Nicotiana tabacum) TGA factor has been shown to participate in plant defense responses upon attack of a variety of pathogens (Thurow et al, 2005), ATB2 has been shown to participate in both sucrose-specific sugar sensing and the signaling system associated with the transport and utilization of metabolites in Arabidopsis (Rook et al, 1998) and HY5 mediates light response in Arabidopsis (Toh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Arabidopsis thaliana genome contains 75 bZIP genes (Jakoby et al 2002), both 89 and 92 have been reported to be present in rice (Oryza sativa; Nijhawan et al 2008;Correa et al 2008), 47 have been identified in soybean (Glycine max; Liao et al 2008), 92 in sorghum (Sorghum bicolor; Wang et al 2011), 125 in maize (Zea mays; Wei et al 2012), 47 (Gao et al 2014) and 55 in grapevine (Vitis vinifera). Plant bZIP TFs are involved in regulating many metabolic processes, such as energy metabolism (Baena-González et al 2007), cell elongation (Fukazawa et al 2000), organ and tissue differentiation (Silveira et al 2007), embryogenesis (Guan et al 2009), floral induction and development (Abe et al 2005;Zou et al 2008), seed maturation (Jakoby et al 2002;Cheng et al 2014), plant senescence (Smykowski et al 2010), hormone signaling (Fujita et al 2005;Kang et al 2002;Kim et al 2004), photomorphogenesis (Huang et al 2012), and light signaling (Mallappa et al 2006). In addition, they control responses to a variety of abiotic stimuli, such as high salinity (Hsieh et al 2010;García et al 2012), drought (Yoshida et al 2010), cold stress ) and heat stress .…”
Section: Introductionmentioning
confidence: 99%